The first mistake [large type] - Jones, Sandie (A Bell Elkins Novel, 2019)
"THE WIFE: For Alice, life has never been better. With her second husband, she has a successful business, two children, and a beautiful house. HER HUSBAND: Alice knows that life could have been different if her first husband had lived, but Nathan's arrival into her life gave her back the happiness she craved. HER BEST FRIEND: Through the ups and downs of life, from celebratory nights out to comforting each other through loss, Alice knows that with her best friend Beth by her side, they can survive anything together. So when Nathan starts acting strangely, Alice turns to Beth for help. But soon, Alice begins to wonder whether her trust has been misplaced . . . The first mistake could be her last"--